Students’ Perspectives on Quality Assurance and Sustainable Higher Education: Evidence from the Faculty of Economics and Business, Universiti Malaysia Sarawak - Farhana, Ismail; Yi Fun, Phang; Nur Zaimah, Ubaidillah (Human Resource Management Academic Research Society, 2025)
This study examines the influence of quality assurance practices on students’ knowledge, skills, competencies, and employability within higher education. Survey data were collected from students at the Faculty of Economics and Business, Universiti Malaysia Sarawak (UNIMAS), and analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. The results indicate that institutional infrastructure, technological facilities, the quality of teaching and learning processes, practical training, and student research activities significantly enhance students’ knowledge, skills, and competencies. Furthermore, student research activities exert a positive and direct effect on employability outcomes. The findings underscore the importance of strengthening quality assurance mechanisms to ensure that higher education institutions effectively contribute to both academic and professional development. Policy implications suggest that improving quality assurance across teaching, learning, and research dimensions is essential to enhance graduate employability, develop key competencies, and foster the sustainability of higher education.